Low-cycle and extremely-low-cycle fatigue behaviors of high-Mn austenitic TRIP/TWIP alloys: Property evaluation, damage mechanisms and life prediction. (15th January 2016) - Shao, C.W.; Zhang, P.; Liu, R.; Zhang, Z.J.; Pang, J.C.; Zhang, Z.F.
Abstract: The cyclic deformation and damage behaviors of the Fe–Mn and Fe–Mn–C TRIP/TWIP steels are comprehensively studied in a wide range of strain amplitude (from 0.3% to 8.0%). It is found that with increasing C content, the dislocation structures change from wavy slip to planar slip after cyclic deformation. In order to evaluate the low-cycle and extremely-low-cycle fatigue (LCF and ELCF) properties, a fatigue life prediction model, N f  = ( W a / W 0 ) β, with a hysteresis energy-based criterion is used and developed. The model reveals that the LCF and ELCF damage mechanisms can be controlled by the material's damage capacity (the intrinsic fatigue toughness W 0 ) and its ability of transforming mechanical work into effective damage (the damage transition exponent β ). From a macroscopic point of view, W 0 is related to the match of strength and ductility (approximately the static toughness U ), and β mainly has a negative correlation with the cyclic strain hardening exponent n ′. On the micro-scale level, W 0 represents the defect-accommodated ability of the materials, and β is determined by the uniformity and reversibility of plastic deformation. For the current Fe–Mn(–C) TRIP/TWIP steels with increasing C content, the cooperation between an increasing damage capacity and an incremental damage accumulation rate leads to a higher ELCF property and a lower LCF property. Graphical abstract: The low-cycle fatigue (LCF) damage mechanisms may be controlled by the material's damage capacity and damage accumulation rate. The influences of planar slip caused by short-range order (SRO) on fatigue damage and cracking are quite different from those caused by lowering the stacking fault energy (SFE), which has its origin from the various effects on damage accumulation rate.